2010
DOI: 10.1515/bot.2010.020
|View full text |Cite
|
Sign up to set email alerts
|

Aerial exposure and desiccation tolerances are correlated to species composition in “green tides” of the Salish Sea (northeastern Pacific)

Abstract: Relatively little is known about the causes of species distribution within macroalgal blooms occurring on or over soft substrata. We examine the roles of aerial exposure and desiccation in determining elevational patterns of two dominant bloom-forming ulvoid algae, Ulva lactuca and Ulvaria obscura, on the northeastern Pacific coast. These species were stressed with constant desiccation time, desiccation to a constant water potential, and desiccation to a fixed water loss. As a measure of health, we examined ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 34 publications
0
6
1
1
Order By: Relevance
“…are well adapted to desiccation stress in comparison with other species (e.g. Johnson et al, 1974;Quadir et al, 1979;Einav et al, 1995;Abe et al, 2001;Guo and Dong, 2008;Nelson et al, 2010). Partial desiccation can elevate photosynthesis (e.g.…”
Section: Temperature and Periods Of Emersionmentioning
confidence: 99%
“…are well adapted to desiccation stress in comparison with other species (e.g. Johnson et al, 1974;Quadir et al, 1979;Einav et al, 1995;Abe et al, 2001;Guo and Dong, 2008;Nelson et al, 2010). Partial desiccation can elevate photosynthesis (e.g.…”
Section: Temperature and Periods Of Emersionmentioning
confidence: 99%
“…Similarly, Abe, Kurashima, Yokohama, and Tanaka (2001) worked on 18 intertidal seaweeds and found that algae from uppermost intertidal zone Porphyra dentata, could fully recover the photosynthetic activity after being desiccated at a water potential of −158 MPa, when compared to those collected from lower intertidal zones. Nelson, Olson, Imhoff, and Nelson (2010) examined the role of aerial exposure in determining the elevation patterns in ulvoid algae, U. lactuca and Ulvaria obscura. Later, Zou and Gao (2002) also observed similar phenomenon with significant decrease in net photosynthesis, dark respiration, photosynthetic efficiency and apparent carboxylating efficiency of Porphyra haitanensis following desiccation exposure during low tide conditions.…”
Section: Effect On Growth Photosynthesis Respiration Morphology Anmentioning
confidence: 99%
“…The major metallic pollutants implicated in culture systems and coastal waters are Pb, Cr, Hg, U, Se, Zn, As, Cd, Au, Ag, Cu and Ni among which Cd is readily absorbed in a combined state with sulphur, chlorine and oxygen and stored in the algal thalli (Komjarova, 2009;Dittert et al, 2012;Renzi et al, 2014). Green macroalgae (Chlorophyta) are known to be a significant biological indicator of heavy metal contamination in marine ecosystems (Nelson et al, 2010). Various studies have demonstrated the use of green macroalgae from the genus Ulva as a bio-filter/monitor of coastal contamination because of their relatively simple morphology, high tissue bioaccumulation, and widespread distribution (Alkhalifa et al, 2012;Zoll and Schijf, 2012;Renzi et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The specific justification of this research has evolved from aquaculture's environmental consequences, and the nutrient enrichment of the outlet water systems associated with more general aquaculture practices. Aquaculture practices generally lead to high nutrient loading that can facilitate changes in the natural dynamics of water bodies and can lead to oxygen depletion, green tide (harmful algal blooms) events, eutrophication, fish kills, low productivity, increased risks of infectious diseases, and deterioration of the groundwater with serious consequences for human health, the environment and economic development (Van Alstyne et al, 2007;Nelson et al, 2010;DEC, 2014;Redmond et al, 2014). In this study, we investigated the nutrient uptake potential, efficiency and bioaccumulation potential of the green macroalga Ulva armoricana in an outdoor, on-land flow-through paddle wheel system.…”
Section: Introductionmentioning
confidence: 99%